Pyrrolo[2, 3-b]quinoxaline with 2-(2-aminoethyl)pyridine chain highly selective fluorescent receptor for Zn2+ exhibiting a dual fluorescence and AIEE in crystalline state. Issue 3 (25th November 2014) - Ostrowska, Katarzyna; Dudek, Łukasz; Grolik, Jarosław; Gryl, Marlena; Stadnicka, Katarzyna
Abstract : The article describes the synthesis of selective dual emissive intramolecular charge transfer (ICT) receptor for zinc ion in acetonitrile, exhibiting aggregation induced emission enhancement (AIEE) in solid state. Abstract : This article describes the synthesis of a selective dual emissive intramolecular charge transfer (ICT) receptor for zinc ion in acetonitrile, exhibiting aggregation induced emission enhancement (AIEE) in the solid state due to the formation of inter- or intra-molecular hydrogen bonds and aromatic donor–acceptor interaction with H- or J-aggregation.